The Credit Crunch and the Digital Bite. - Holmes, Neville (Computer (00189162), 2009)
This article discusses the role played by computer software programming in the development of the 2008 financial crisis. The history of financial products such as paper currency, foreign exchange options, and credit-default swaps is described. The tendency of financial institutions to manipulate investment instruments based on inadequate risk assessment is noted. The author believes that computer engineers bear responsibility for the financial crisis insofar as they understood the underlying financial instruments that their programs were being used to design.